Impacted Canines: Our Clinical Experience - Chawla, Sonia (Int J Clin Pediatr Dent, 2011)
BACKGROUND: To discuss the management of impacted canines and the various approaches used for the same. MATERIALS AND METHODS: The data of 33 cases, with 43 impacted canine teeth, seen and operated over a period of 3-year in Santosh Dental College and Hospital has been compiled. The diagnostic methods and treatment modalities undertaken are described and discussed. RESULTS: Canine impactions were more common in the maxilla as compared with mandible in our study, which was statistically significant. Impacted canine position was mostly palatal in maxilla and labial in mandible. Chi-square test yielded a p-value of 0.002 which shows that there is an association between arch and position. The treatment options used were surgical exposure and orthodontic repositioning, cyst enucleation with extraction of impacted canine and surgical removal of impacted canine. CONCLUSION: Surgical exposure and orthodontic repositioning was successfully applied as first-line treatment for correcting ectopic positioned canine. In cases where exposure and subsequent orthodontic treatment was not indicated, the impacted canine was surgically removed to prevent future problems and surgical procedure was designed according to position of impacted canine.